Scaling up: The politics of health and place - Bambra, Clare; Smith, Katherine E.; Pearce, Jamie (Social science & medicine (1982), 2019)
Research into the role of place in shaping inequalities in health has focused largely on examining individual and/or localised drivers, often using a context-composition framing. Whilst this body of work has advanced considerably our understanding of the effects of local environments on health, and re-established an awareness of the importance of place for health, it has done so at the expense of marginalising and minimising the influences of macro political and economic structures on both place and health. In this paper, we argue that: (i) we need to scale up our analysis, moving beyond merely analysing local horizontal drivers to take wider, vertical structural factors into account; and (ii) if we are serious about reducing place-based health inequalities, such analysis needs be overtly linked to appropriate policy levers. Drawing on three case studies (the US mortality disadvantage, Scotland's excess mortality, and regional health divides in England and Germany) we outline the theoretical and empirical value of taking a more political economy approach to understanding geographical inequalities in health. We conclude by outlining the implications for future research and for efforts to influence policy from ‘scaling up’ geographical research into health inequalities. •Health-place research commonly examines focuses individual and/or localised drivers.•Health geography should ‘scale up’ analysis of health-place relationships.•Research needs to account for wider, vertical and structural factors.•Political economic approaches add value to insight on geographic health inequalities.•Considers the policy implications of taking a political economy approach.